THE NATURE OF DESTRUCTIVE ORGANIZATIONAL BEHAVIOR: THEORIES OF NATURALIST ANTHROPOLOGY - Y. A. Gorbunova; I. V. Deviatovskaia (Дискурс)
The purpose of the article is to analyze the nature of destructive organizational behavior in the context of naturalist anthropology. Corporate anthropology focuses on unique aspects of organizational behavior, adopting ethnomethodology, culture anthropology and microsociology approaches. In turn, philosophical anthropology allows to see the general, universal in the destructive behavior of the staff. The article analyzes anthropological grounds of socio-psychological vandalism as a form of destructive behavior of personnel. In the framework of philosophical anthropology and naturalistic discourse specifically, the reduction of the vital principle of man towards aggression and destructiveness is criticized, and the nature of man is claimed to possess creative and constructive orientations. The idea that human nature is ambivalent and is a determinant of destructive organizational behavior and, at the same time, possesses resources to overcome the destructiveness, is proved.